PERSPEKTYWY ROZWOJU RYNKU LOFTÓW W KRAKOWIE - Chaberko, Tomasz (Space – Society – Economy, 2012)
Loft is a type of large and spacious apartment adopted, modernized and rendered for the residential use. Loft apartments, as an integral part of former industrial buildings, have evolved to be a significant asset on the housing market all around Poland, especially in urban areas. Łódź and Żyrardów hold the largest supply and most prospective opportunities for loft market development, although such investments have also been made in Bytom, Warsaw, Wrocław and Zielona Góra. This study examines contemporary “loft-style” residential development in Cracow with a special regard to the post-industrial buildings presently being converted to lofts. The author looks on existing and planned loft investments through the lenses of future renewal and regeneration of postindustrial areas. The issues discussed in this study include: the scale of investments (number of apartments, size of apartments), various ways of adapting industrial buildings (with a special regard to historic structures and their preservation) and presence of such components as: parking lots and commercial space. Existing and planned lofts are exceptional for the housing market; thus create a great chance for developers to be distinguished and recognized by affluent homebuyers. However, a small number of adaptable postindustrial buildings, especially those of high architectural value, results in rather a meager chance for development of loft market in the city of Cracow.